2015
DOI: 10.17219/dmp/58943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Parameters of Oral Cavity, Physical and Microbiological Properties of Saliva in Patients with Obesity

Abstract: A -koncepcja i projekt badania, B -gromadzenie i/lub zestawianie danych, C -analiza i interpretacja danych, D -napisanie artykułu, E -krytyczne zrecenzowanie artykułu, F -zatwierdzenie ostatecznej wersji artykułu StreszczenieWprowadzenie. Wyniki wielu badań wskazują na związek otyłości nie tylko z chorobami ogólnoustrojowymi, ale również ze zmianami w środowisku jamy ustnej. Cel pracy. Kliniczna ocena stanu jamy ustnej, ilości wydzielanej śliny, miana bakterii Streptococcus mutans i Lactobacillus spp. oraz ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…26 Also, the results of the study conducted in a group of adults by Lehmann-Kalata et al confirmed decreased stimulated and unstimulated saliva secretion in obese people compared to those with normal body weight. 32 In the study conducted by Rodríguez et al, 67 the secretion of unstimulated saliva, and in the study of de Campos et al, 68 the secretion of both unstimulated and stimulated saliva did not differ significantly in the group of obese children and children with normal body weight. However, Rodríguez et al observed that unstimulated saliva secretion was considerably higher in obese girls than in obese boys, which was not observed in a group of adolescents with normal body weight.…”
Section: Changes In the Quantitative Composition Of Saliva In Obese Cmentioning
confidence: 86%
See 2 more Smart Citations
“…26 Also, the results of the study conducted in a group of adults by Lehmann-Kalata et al confirmed decreased stimulated and unstimulated saliva secretion in obese people compared to those with normal body weight. 32 In the study conducted by Rodríguez et al, 67 the secretion of unstimulated saliva, and in the study of de Campos et al, 68 the secretion of both unstimulated and stimulated saliva did not differ significantly in the group of obese children and children with normal body weight. However, Rodríguez et al observed that unstimulated saliva secretion was considerably higher in obese girls than in obese boys, which was not observed in a group of adolescents with normal body weight.…”
Section: Changes In the Quantitative Composition Of Saliva In Obese Cmentioning
confidence: 86%
“…The study by Lehmann-Kalata et al showed a statistically significant increase in the gingival index (GI) and sulcus bleeding index (SBI) values in obese people in comparison to those with normal body weight. 32 The study by Zeigler et al showed no correlation between BMI, dietary habits, hygiene, and oral hygiene in obese adolescents. 33 However, obese teenagers with gingival pocket depth (PD) ≥4 mm had significantly more points with BOP ≥ 25% and considerably higher systolic blood pressure than obese teenagers with PD < 4 mm.…”
Section: Obesity and Periodontal Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…The proportions of most of these pathogens, as well as Campylobacter rectus and Eikenella corrodens , increased at the disease sites of obese patients compared to those of normal weight. Lehmann-Kalata et al ( 58 , have reported a statistically significant correlation between increased levels of Streptococcus mutans and Lactobacillus spp. in obese patients compared to patients of normal weight.…”
Section: Obesity and Prevalent Pathologies Of Oral Cavitymentioning
confidence: 96%
“…Lehmann-Kalata et al . ( 58 , reported a higher incidence of dental caries, and a worse state of the gums and oral hygiene in obese patients than in those of normal weight. Additionally, the latter had a significantly greater amount of stimulated and non-stimulated saliva than the obese patients, there being a statistically significant correlation between the increase in Streptococcus mutans and Lactobacillus spp.…”
Section: Obesity and Prevalent Pathologies Of Oral Cavitymentioning
confidence: 98%